European Biological Variation Study (EuBIVAS): Within- and Between-Subject Biological Variation Data for 15 Frequently Measured Proteins. (1st August 2019) - Carobene, Anna; Aarsand, Aasne K; Guerra, Elena; Bartlett, William A; Coşkun, Abdurrahman; Díaz-Garzón, Jorge; Fernandez-Calle, Pilar; Jonker, Niels; Locatelli, Massimo; Sandberg, Sverre; Ceriotti, Ferruccio
Abstract: BACKGROUND: The European Biological Variation Study (EuBIVAS) was established to deliver rigorously determined data for biological variation (BV). Here, EuBIVAS-based BV estimates are provided for α1 -acid glycoprotein, α1 -antitrypsin, albumin, β2 -microglobulin, ceruloplasmin, complement component 3, complement component 4, C-reactive protein (CRP), cystatin C, haptoglobin, IgA, IgG, IgM, soluble transferrin receptor (sTfR), and transferrin (Trf), together with their associated analytical performance specifications (APSs) and reference change values (RCVs). METHOD: Serum samples from weekly blood samplings of 91 healthy study participants (38 males and 53 females, ages 21–69 years old) over 10 consecutive weeks in 6 European laboratories were stored at −80 °C before duplicate analysis on a Roche Cobas c702. Outlier and variance homogeneity analyses were performed followed by CV-ANOVA on trend-corrected data if relevant, to determine BV and analytical variation estimates with CI and the associated RCV. RESULTS: For the acute phase proteins, several participants experienced mild inflammatory episodes during the study, requiring exclusion of 7% of the 25290 results. Within-subject BV (CVI ) estimates for specific proteins obtained in our study were lower than those available in the online 2014 BV database, except for Trf, whereas between-subject BV (CVG ) estimates were similar. CVI and CVG estimates for sTfR, which have not previously been published, were 6.0% and 19.1%, respectively. CONCLUSIONS: In addition to new BV estimates for sTfR, this EuBIVAS substudy generated more demanding APS for frequently requested plasma specific proteins. APS for CRP should not be calculated from BV data except when CRP is used as a risk factor for cardiovascular disease.